Photocatalytic and photoelectrochemical treatment effects on the killing of escherichia coli cells - Ribeiro, M. A. [UNESP]; Bidoia, E. D. [UNESP] (My University, 2005)
In this study, we report the efficiency of photocatalytic and photoelectrochemical treatment using titanium dioxide as semiconductor and its applications in water disinfection. It was compared the efficiency of the two methods on the killing of E.coli cells. The photoelectrochemical treatment with electric field enhancement showed a good result and could be a new technology to water treatment.
Keywords: Disinfection; Escherichia coli; Photocatalysis; Titanium dioxide; E.coli cells; Electric field enhancement; Escherichia coli cells; Photo-catalytic; Photoelectrochemical treatment; Water disinfections; Electric fields; Oxides